2019
DOI: 10.1093/gastro/goz038
|View full text |Cite|
|
Sign up to set email alerts
|

Association between matrix Gla protein and ulcerative colitis according to DNA microarray data

Abstract: Background Matrix Gla protein (MGP) is a secreted protein contributed to the immunomodulatory functions of mesenchymal stromal cells. Microarray profiling found a significantly higher expression level of the extracellular matrix gene MGP in patients with ulcerative colitis (UC). However, little is known about the role of MGP in UC and its upstream signaling regulation. This study aimed to identify the expression of MGP in UC and its upstream regulator mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Our findings could be implying that increased IBD activity up regulates MGP through complex inflammatory mechanisms, but due to possible vitamin K deficiency, the peptide cannot be fully activated and therefore loses its inhibitory effect on vascular calcification. This would be in line with the results of a Danish cohort study, which reported that flares and persistent IBD activity increases the risk of myocardial infarction, stroke and cardiovascular death[ 49 ], and the previously mentioned study on UC patients which showed that the expression of MGP mRNA increases with the disease severity[ 24 ]. Moreover, after division of patients with IBD into tertiles depending on hsCRP levels and FC levels our study showed in both cases significantly higher plasma levels of dp-ucMGP in the 3 rd tertile compared to the 1 st and 2 nd tertiles which further indicates the possible association of dp-ucMGP with the IBD activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings could be implying that increased IBD activity up regulates MGP through complex inflammatory mechanisms, but due to possible vitamin K deficiency, the peptide cannot be fully activated and therefore loses its inhibitory effect on vascular calcification. This would be in line with the results of a Danish cohort study, which reported that flares and persistent IBD activity increases the risk of myocardial infarction, stroke and cardiovascular death[ 49 ], and the previously mentioned study on UC patients which showed that the expression of MGP mRNA increases with the disease severity[ 24 ]. Moreover, after division of patients with IBD into tertiles depending on hsCRP levels and FC levels our study showed in both cases significantly higher plasma levels of dp-ucMGP in the 3 rd tertile compared to the 1 st and 2 nd tertiles which further indicates the possible association of dp-ucMGP with the IBD activity.…”
Section: Discussionsupporting
confidence: 88%
“…Given results are in line with the outcomes of a recent study conducted on human patients with UC and on mice with dextran sulfate sodium (DSS) induced colitis[ 24 ]. They showed that MGP mRNA levels are significantly higher in both UC patients and DSS-induced colitis mice compared to their control groups.…”
Section: Discussionsupporting
confidence: 80%
“… 38–41 Dong et al found increased gene expression and activation levels of EGR1 in biopsies from UC patients, compared to healthy controls. 42 Also MYC, another top three transcription factors, was found at higher levels in biopsies from patients with IBD by Macpherson et al and linked to altered cell cycle control due to inflammatory processes. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Compared to the healthy control group, plasma levels of dp-ucMGP were significantly higher in IBD patients and positively correlated with high sensitivity C-reactive protein (hsCRP) levels ( 221 ). The expression of MGP, which can be upregulated by a conserved binding site for Egr-1 in the upstream region of the human MGP gene, was positively correlated with disease severity of UC patients and DSS-induced colitis rats ( 222 ). MGP was upregulated in different stages of colon cancer and associated with a worse prognosis ( 223 ).…”
Section: Vk In Intestinal Health and Diseasementioning
confidence: 99%